Isotope substitution effects on the magnetic compass properties of cryptochrome-based radical pairs: a computational study - Pazera, G; Benjamin, P; Mouritsen, H; Hore, P (American Chemical Society, 2023)
The biophysical mechanism of the magnetic compass sense of migratory songbirds is thought to rely on the photochemical reactions of flavin-containing radical pairs in cryptochrome proteins located in the birds’ eyes. A consequence of this hypothesis is that the effect of the Earth’s magnetic field on the quantum yields of reaction products should be sensitive to isotopic substitutions that modify the hyperfine interactions in the radicals. In this report, we use spin dynamics simulations to explore the effects of 1H → 2H, 12C → 13C, and 14N → 15N isotopic substitutions on the functioning of cryptochrome 4a as a magnetic direction sensor. Two main conclusions emerge. (1) Uniform deuteration of the flavin chromophore appears to be the best way to boost the anisotropy of the magnetic field effect and to change its symmetry. (2) 13C substitution of three of the 12 flavin carbons, in particular C4, C4a, and C8α, seems to be the best recipe for attenuating the anisotropy. These predictions should give insight into the factors that control the magnetic sensitivity once spectroscopic techniques are available for measuring magnetic field effects on oriented protein samples.